2002
DOI: 10.1159/000066321
|View full text |Cite
|
Sign up to set email alerts
|

Human Paraoxonase1 Gene Polymorphisms and the Risk of Coronary Heart Disease: A Community-Based Study

Abstract: Published data on the association between paraoxonase1 (PON1) polymorphisms and coronary heart disease (CHD) have yielded controversial results. The objective of this study was to determine the possible relationship between the two human PON1 amino acid variants, the Leu55Met and the Gln192Arg polymorphism, and the risk of CHD in a community-dwelling cohort of European ancestry. PON1 genotypes of 152 women and 151 men out of 1,998 randomly selected individuals aged 44–75 years were determined by polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
0
13
1
3
Order By: Relevance
“…The PON1 activity in patients with CHD is approximately half that in disease-free control participants (28). Low PON1 activity increases the development of atherosclerosis (353). The group of men with the highest levels of serum PON1 activity were nearly 60% less likely to have CHD than those with the lowest (205).…”
Section: Pon Activity Decreases Atherosclerosismentioning
confidence: 97%
See 2 more Smart Citations
“…The PON1 activity in patients with CHD is approximately half that in disease-free control participants (28). Low PON1 activity increases the development of atherosclerosis (353). The group of men with the highest levels of serum PON1 activity were nearly 60% less likely to have CHD than those with the lowest (205).…”
Section: Pon Activity Decreases Atherosclerosismentioning
confidence: 97%
“…However, some studies claim that no association between PON1 polymorphisms and plasma lipoproteins exists (48,204,353). Contradictions among the results from different studies could result from partially intrinsic differences in serum PON levels among populations.…”
Section: Pons Polymorphisms and Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…35,36 However, other studies showed no association between these PON polymorphisms and plasma lipoproteins. 37,38 A study investigating the association between PON192 polymorphism and serum lipid levels in Turkish CAD patients also failed to show any significant results. 29 In the present study, regarding the comparison of serum lipid levels between CAD patients and the controls with regard to polymorphic allele, the most significant results were in HDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic epidemiology studies on the polymorphisms L55M and Q192R have previously reported confl icting data regarding effects on plasma lipoproteins (30)(31)(32). A specifi c search in the published genome wide association studies found no reported association of the PON1 genetic locus with lipids, BP, or any other of the reported parameters.…”
Section: Pon1 and Plasma Lipids/lipoproteinsmentioning
confidence: 99%